1998
DOI: 10.1172/jci562
|View full text |Cite
|
Sign up to set email alerts
|

Platelet microbicidal proteins and neutrophil defensin disrupt the Staphylococcus aureus cytoplasmic membrane by distinct mechanisms of action.

Abstract: Platelet microbicidal proteins (PMPs) are hypothesized to exert microbicidal effects via cytoplasmic membrane disruption. Transmission electron microscopy demonstrated a temporal association between PMP exposure, damage of the Staphylococcus aureus cytoplasmic membrane ultrastructure, and subsequent cell death. To investigate the mechanisms of action of PMPs leading to membrane damage, we used flow cytometry to compare the effects of two distinct PMPs (thrombin-induced PMP-1 [tPMP-1] or PMP-2) with human neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
175
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(187 citation statements)
references
References 37 publications
10
175
2
Order By: Relevance
“…Furthermore, Yeaman et al [57] and Tang et al [58] support the idea that platelets also are involved in microbicidal activity, suggesting that they play a role in the platelet host defense mechanism by releasing a variety of platelet microbicidal proteins. The platelet microbicidal proteins were shown to be released after platelet acti-vation, demonstrating potent activities against pathogens that have a tendency to enter the bloodstream [59].…”
Section: Infection Preventionmentioning
confidence: 91%
“…Furthermore, Yeaman et al [57] and Tang et al [58] support the idea that platelets also are involved in microbicidal activity, suggesting that they play a role in the platelet host defense mechanism by releasing a variety of platelet microbicidal proteins. The platelet microbicidal proteins were shown to be released after platelet acti-vation, demonstrating potent activities against pathogens that have a tendency to enter the bloodstream [59].…”
Section: Infection Preventionmentioning
confidence: 91%
“…Recently, it was demonstrated that telavancin's antibacterial activity derives from at least two mechanisms of action. The second mechanism of action of telavancin is related to perturbation of the electrochemical potential and permeability of the bacterial cell membrane, causing membrane permeabilization similarly to the mode of action of antimicrobial peptides [40,102,104,105]. Dissipation of the cell membrane potential is concentration-dependent, rapid (15 minutes), and can be detected starting with telavancin at its 10-fold MIC values [102].…”
Section: Semi-synthetic Lipoglycopeptidesmentioning
confidence: 99%
“…Microorganisms constitutively resist the action of AMPs by using different mechanisms, for example resistance strains of Staphylococcus aureuscontain high D-alanylation of lipoteichoic acid with positively charged amine groups resulted in lowering the membrane negatively charge so lack of electrostatic affinity for AMPs toward membranes [45], another mechanism by membrane energy alteration, studies reports that microorganisms with altered membrane energetic are more resistance to AMPs action than microorganisms with normal membrane energy status, such as Candida albicans a respiratory deficient mutant fungi with membrane energy altered by lowered mitochondrial ATP synthesis [46] and S. aureus with membrane energy altered by constitutively reduced transmembrane potential [47]. Electrostatic shielding mechanism used also by microorganisms to resist the action of AMPs in which membranes have been covered with highly anionic glycocalyx or special capsule resulted in shield the lipid bilayer from AMPs [19].…”
Section: Resistance To Antimicrobial Peptidesmentioning
confidence: 99%